High-temperature-resistant electromagnetic shielding and heat-conducting film and preparation method thereof
Patent Information
- Application Number
- CN202611395755.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-16
AI Technical Summary
1、本发明将苯并噁嗪,石墨烯与氮化硼组装制备薄膜,通过真空过滤制备,工艺简单。经过绝缘的苯并噁嗪/氮化硼层包覆,有效的解决了苯并噁嗪/石墨烯层导电的缺陷。片层状的碳基填料在苯并噁嗪的连接下堆叠排列,表现出优异的取向结构。得益于这种结构,电磁波射入薄膜后,在片层间将被多次反射消耗,具有优异的电磁屏蔽性能。
Smart Images

Figure CN122917486A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of composite material thin film technology, and more specifically, it relates to a high-temperature resistant electromagnetic shielding thermally conductive thin film and its preparation method. Background Technology
[0002] With the full commercialization of fifth-generation (5G) mobile communication technology and the research and development of sixth-generation (6G) technology, human society is gradually entering a highly information-based development stage. The types and quantities of consumer electronics products are showing a rapid growth trend. While improving the convenience of life and production efficiency, this also leads to a continuous increase in the level of electromagnetic radiation in the environment. The electromagnetic interference (EMI) problem caused by complex electromagnetic environments is becoming increasingly prominent. This can not only cause data loss and malfunctions in electronic devices, but long-term exposure to high-intensity electromagnetic fields may also have potential impacts on human health. Ideal electromagnetic shielding materials should be based on absorption mechanisms, converting electromagnetic wave energy into heat energy or other forms of energy and dissipating them, thereby reducing secondary pollution caused by electromagnetic wave reflection.
[0003] In early research, traditional metals such as copper, aluminum, and silver were widely used in electromagnetic interference shielding due to their excellent electrical conductivity. However, these metals generally suffer from high density, complex processing, and limited corrosion resistance, making it difficult to meet the lightweight and structural flexibility requirements of aerospace equipment and portable electronic devices. With the rapid development of flexible electronics and wearable devices, the demand for materials that combine lightweight, flexibility, and high-efficiency shielding performance is becoming increasingly urgent. As electronic devices develop towards higher integration, higher frequency, and higher power, electromagnetic shielding materials need to have good thermal management capabilities and electrical insulation while playing an electromagnetic protection role. If the heat generated under high-density packaging conditions cannot be dissipated in time, it will accelerate device aging and reduce system operational stability. Summary of the Invention
[0004] In order to improve the electromagnetic shielding performance, thermal conductivity and high temperature resistance of electromagnetic shielding thermal conductive films, this application provides a high temperature resistant electromagnetic shielding thermal conductive film and its preparation method.
[0005] In a first aspect, this application provides a high-temperature resistant electromagnetic shielding thermally conductive film, employing the following technical solution: A high-temperature resistant electromagnetic shielding and thermally conductive film comprises the following raw materials: benzoxazine containing hydrazide groups, graphene, and boron nitride, wherein the structure of the benzoxazine containing hydrazide groups is shown below: .
[0006] By adopting the above technical solution, the benzoxazine containing hydrazide groups contains hydrazide groups and benzoxazine ring structures. The hydrazide groups contain NH hydrogen bond donors, and the amino groups on the surface of amino-modified boron nitride simultaneously contain NH donors and N lone pair electron acceptors. The two can form stable intermolecular hydrogen bonds, improving the compatibility between boron nitride and the matrix interface. At the same time, the aromatic ring structure of benzoxazine can form π-π conjugation with the conjugated structure of graphene. Under the synergistic influence of hydrogen bonding and conjugation, the benzoxazine containing hydrazide groups can simultaneously assemble with amino-modified hexagonal boron nitride and graphene to form a stable three-dimensional network structure. Graphene provides excellent electrical conductivity and electromagnetic shielding properties, while boron nitride provides good thermal conductivity and electrical insulation properties. The benzoxazine containing hydrazide groups, as a connecting medium and matrix material, forms a cross-linked network after high-temperature curing, improving the heat resistance and mechanical properties of the composite material. The synergistic effect of the three components makes the prepared film possess excellent electromagnetic shielding properties, thermal conductivity, electrical insulation properties, and high-temperature resistance.
[0007] Secondly, this application provides a method for preparing a high-temperature resistant electromagnetic shielding thermally conductive thin film, employing the following technical solution: A method for preparing a high-temperature resistant electromagnetic shielding thermally conductive thin film includes the following steps: (1) Add isophthalic acid dihydrazide, phenol and paraformaldehyde to an organic solvent, heat to react, filter the reactants after the reaction, wash the filtrate and dry it by rotary evaporation to obtain a solid product, which is benzoxazine containing hydrazide group; (2) Boron nitride and urea were ball-milled, centrifuged and dried to obtain amino-modified hexagonal boron nitride; (3) The benzoxazine containing hydrazide group obtained in step (1) is mixed and stirred with graphene dispersion and amino-modified hexagonal boron nitride obtained in step (2). The mixture is then filtered through vacuum and self-assembled into a film. Finally, it is heated and cured to obtain an insulating electromagnetic shielding composite film material.
[0008] By employing the above technical solution, a benzoxazine monomer containing an acylhydrazine group was first synthesized. Then, amino groups were introduced onto the surface of boron nitride through ball milling and urea modification to obtain amino-modified hexagonal boron nitride. The introduction of amino groups provides interaction sites for subsequent hydrogen bonding with the benzoxazine containing the acylhydrazine group. During assembly, the benzoxazine containing the acylhydrazine group pre-assembled with graphene and amino-modified boron nitride through π-π conjugation and hydrogen bonding to form a uniformly dispersed mixture. Through vacuum filtration self-assembly, the layered graphene and boron nitride were stacked layer by layer under the connection of the benzoxazine containing the acylhydrazine group, exhibiting an excellent orientation structure. Thanks to this ordered layered structure, electromagnetic waves are reflected and absorbed multiple times between the layers after entering the film, thus obtaining excellent electromagnetic shielding performance. Finally, through stepped temperature curing, the benzoxazine containing the acylhydrazine group underwent ring-opening polymerization, forming a cross-linked network between the layers, further enhancing the bonding force between the fillers and the heat resistance of the film.
[0009] Preferably, in step (1), the molar ratio of isophthalic acid dihydrazide, paraformaldehyde, and phenol is 1:(4-4.4):2.
[0010] By adopting the above technical solution and controlling the molar ratio of isophthalic acid dihydrazide, paraformaldehyde, and phenol within the above range, the Mannich reaction can be fully carried out, and the yield and purity of benzoxazine containing hydrazide groups can be improved. The appropriate excess of paraformaldehyde is beneficial to the complete reaction. The amount of phenol is twice that of isophthalic acid dihydrazide, which can ensure that benzoxazine ring structures can be formed at both ends of each hydrazide group.
[0011] Preferably, in step (1), the organic solvent is selected from any one of toluene, N-methylpyrrolidone or N,N-dimethylformamide; the heating reaction temperature is 80-120℃ and the time is 6-10h.
[0012] By adopting the above technical solution, the organic solvent can effectively dissolve the reactants and products, providing a homogeneous reaction environment. The reaction temperature and time are controlled within the above range, which not only ensures the reaction rate and yield but also avoids the occurrence of side reactions.
[0013] Preferably, in step (2), the mass ratio of boron nitride to urea is 1:30; the centrifugation is performed twice, with the first centrifugation speed being 1000-2500 rpm and the second centrifugation speed being 8000-10000 rpm.
[0014] By adopting the above technical solution, urea is assisted in stripping boron nitride during ball milling, and amino groups are introduced on the surface of boron nitride. A two-step centrifugation method is used: the first low-speed centrifugation is used to remove large boron nitride particles that have not been fully stripped, and the second high-speed centrifugation is used to collect smaller, better modified amino-modified hexagonal boron nitride, thereby obtaining a uniform modified boron nitride product.
[0015] Preferably, in step (3), the mass ratio of boron nitride to benzoxazine containing hydrazide is 1:(0.5-3), the mass ratio of graphene to benzoxazine containing hydrazide is 1:(0.25-4), and the mixture is stirred at room temperature for 17-24 hours.
[0016] By adopting the above technical solution, controlling the mass ratio of boron nitride to benzoxazine containing hydrazide and graphene to benzoxazine containing hydrazide within the above range can ensure sufficient assembly among the three components. Insufficient amount of benzoxazine containing hydrazide will lead to insufficient connection and weak bonding between fillers; excessive amount will affect the continuity of the conductive and thermally conductive networks.
[0017] Preferably, in step (3), the vacuum filtration self-assembly is performed by suction filtration in a Buchner core funnel, and the film obtained after suction filtration is dried in a vacuum drying oven.
[0018] By adopting the above technical solutions, the Buchner sand core funnel can provide a uniform filtration surface. The vacuum filtration process causes the sheet packing to be stacked in an orderly manner in the filtration direction, forming an oriented layered structure. Vacuum drying can effectively remove residual solvents and avoid defects in the membrane during the drying process.
[0019] Preferably, in step (2), the specific heating process for curing is as follows: heating to 140℃ and holding for 1 hour, 160℃ and holding for 1 hour, 180℃ and holding for 1 hour, 200℃ and holding for 1 hour, and 240℃ and holding for 1 hour in sequence.
[0020] By adopting the above technical solution and using a stepped heating curing method, benzoxazine containing hydrazide groups is gradually ring-opened and polymerized at different temperatures. The ring-opening polymerization of benzoxazine usually starts above 160℃. Stepped heating is beneficial to control the polymerization rate and avoid internal stress and defects caused by excessively fast polymerization. Finally, the polymerization reaction is completed by holding at 240℃ for 1 hour, forming a highly cross-linked network structure, which endows the film with excellent high-temperature resistance and mechanical properties.
[0021] Thirdly, this application provides an application of a high-temperature resistant electromagnetic shielding thermally conductive film, employing the following technical solution: Application of a high-temperature resistant electromagnetic shielding thermally conductive film in chip packaging and protective materials for electronic control units of new energy vehicles.
[0022] By adopting the above technical solutions, the electromagnetic shielding thermal conductive film has excellent electromagnetic shielding performance, thermal conductivity, electrical insulation performance and high temperature resistance, which can meet the dual requirements of chip packaging and new energy vehicle electronic control units for electromagnetic protection and thermal management.
[0023] In summary, this application has the following beneficial effects: 1. This invention assembles benzoxazine, graphene, and boron nitride to prepare a thin film via vacuum filtration, a simple process. The insulating benzoxazine / boron nitride layer effectively overcomes the conductivity defect of the benzoxazine / graphene layer. The layered carbon-based fillers, linked by the benzoxazine, exhibit excellent orientation. Thanks to this structure, electromagnetic waves incident on the film are repeatedly reflected and dissipated between the layers, resulting in excellent electromagnetic shielding performance.
[0024] 2. In the benzoxazine / carbon material thin film system containing hydrazide groups prepared by this invention, boron nitride and benzoxazine containing hydrazide groups are assembled under the synergistic influence of hydrogen bonding and conjugation. Graphene and benzoxazine containing hydrazide groups self-assemble through conjugation. Graphene and benzoxazine containing hydrazide groups complete assembly through π-π conjugation. Amino-modified boron nitride and benzoxazine containing hydrazide groups complete assembly through intermolecular hydrogen bonds. The two types of filler layers are tightly bonded by the cross-linked network of benzoxazine after curing. In subsequent heat treatment, the benzoxazine containing hydrazide groups undergoes ring-opening upon heating, cross-linking between the layers, and enhancing the bonding force between the fillers. Attached Figure Description
[0025] Figure 1 This is the 1H NMR spectrum of the benzoxazine containing an acylhydrazine group in Example 1; Figure 2 This is a TGA image of the benzoxazine resin containing hydrazide groups and the electromagnetic shielding thermally conductive film in Example 1; Figure 3 This is an SEM image of the electromagnetic shielding thermally conductive film in Example 1; Figure 4 This is a comparison chart of the electromagnetic shielding efficiency of the electromagnetic shielding thermal conductive film in Example 1 at 8-12Hz. Detailed Implementation
[0026] The present application will be further described in detail below with reference to the accompanying drawings and embodiments.
[0027] Example
[0028] Example 1 A high-temperature resistant electromagnetic shielding and thermally conductive film comprises the following raw materials: benzoxazine containing hydrazide groups, graphene, and boron nitride. The structure of the benzoxazine containing hydrazide groups is shown below: .
[0029] The preparation method of the above-mentioned high-temperature resistant electromagnetic shielding thermally conductive film includes the following steps: (1) At room temperature, 0.02 mol of isophthalic acid dihydrazide, 0.04 mol of phenol and 0.088 mol of paraformaldehyde were added to a flask, and 100 mL of N,N-dimethylformamide was added. The mixture was stirred at 90 °C and reacted for 10 h. After the reaction, the mixture was filtered, and the filtrate was washed with water three times and then rotary evaporated. The filtrate was dried in a vacuum drying oven at 50 °C for 1 day to obtain benzoxazine containing hydrazide group with a yield of 91%. (2) 1g boron nitride, 30g urea and 80mL deionized water were ball-milled in a ball mill at 400rpm for 24h. After ball milling, the solution was filtered and washed with water until neutral. The washed modified boron nitride was dispersed in water and centrifuged at 1500rpm for 10min. The upper layer solution was taken and centrifuged at 9000rpm for 15min to obtain amino-modified hexagonal boron nitride. (3) At room temperature, N-methylpyrrolidone was added to 100 mL of 20 mL of 1 mg / mL graphene dispersion, the graphene concentration was 0.2 mg / mL, ultrasonically dispersed for 15 min, 20 mg of benzoxazine containing hydrazide group was added, and stirred at room temperature for 20 h to obtain component A; 40 mg of amino-modified hexagonal boron nitride was ultrasonically dispersed in 200 mL of N-methylpyrrolidone solution, and 40 mg of benzoxazine containing hydrazide group was added. The mixture was stirred at room temperature for 20 h to obtain component B. Measure 100 mL of component B and pour it into a Buchner sand core funnel. Filter for 1 hour. Then add all of component A and continue filtering for 2 hours. Finally, add all of the remaining component B and filter for another 7 hours. The film obtained after filtration was vacuum dried at 80℃ for 12 hours, and then heated to open the ring and solidify to obtain a high-temperature resistant electromagnetic shielding thermally conductive film. The specific heating steps for the heating to open the ring and solidify were as follows: heating to 140℃ and holding for 1 hour, 160℃ and holding for 1 hour, 180℃ and holding for 1 hour, 200℃ and holding for 1 hour, and 240℃ and holding for 1 hour in sequence.
[0030] Example 2
[0031] A high-temperature resistant electromagnetic shielding and thermally conductive film comprises the following raw materials: benzoxazine containing hydrazide groups, graphene, and boron nitride. The structure of the benzoxazine containing hydrazide groups is shown below: .
[0032] The preparation method of the above-mentioned high-temperature resistant electromagnetic shielding thermally conductive film includes the following steps: (1) At room temperature, 0.02 mol isophthalic acid dihydrazide, 0.04 mol phenol and 0.088 mol paraformaldehyde were added to a flask, and 120 mL toluene was added. The mixture was stirred at 110 °C and reacted for 8 h. After the reaction, the mixture was filtered, the filtrate was washed with water 3 times and then rotary evaporated. The filtrate was dried in a vacuum drying oven at 50 °C for 1 day to obtain benzoxazine containing hydrazide group with a yield of 82%. (2) 1g boron nitride, 30g urea and 80mL deionized water were ball-milled in a ball mill at 400rpm for 24h. After ball milling, the solution was filtered and washed with water until neutral. The washed modified boron nitride was dispersed in water and centrifuged at 2000rpm for 10min. The upper layer solution was taken and centrifuged at 10000rpm for 15min to obtain amino-modified hexagonal boron nitride. (3) At room temperature, N-methylpyrrolidone was added to 100 mL of 20 mL of 1 mg / mL graphene dispersion, the graphene concentration was 0.2 mg / mL, ultrasonically dispersed for 15 min, 10 mg of benzoxazine containing hydrazide group was added, and stirred at room temperature for 18 h to obtain component A; 40 mg of amino-modified hexagonal boron nitride was ultrasonically dispersed in 200 mL of N-methylpyrrolidone solution, and 20 mg of benzoxazine containing hydrazide group was added. The mixture was stirred at room temperature for 20 h to obtain component B. Measure 100 mL of component B and pour it into a Buchner sand core funnel. Filter for 1 hour. Then add all of component A and continue filtering for 2 hours. Finally, add all of the remaining component B and filter for another 7 hours. The film obtained after filtration was vacuum dried at 80℃ for 12 hours, and then heated to open the ring and solidify to obtain a high-temperature resistant electromagnetic shielding thermally conductive film. The specific heating steps for the heating to open the ring and solidify were as follows: heating to 140℃ and holding for 1 hour, 160℃ and holding for 1 hour, 180℃ and holding for 1 hour, 200℃ and holding for 1 hour, and 240℃ and holding for 1 hour in sequence.
[0033] Example 3
[0034] The difference between Example 3 and Example 1 is that in Example 3, the amount of graphene dispersion added in component A is 20 mL, and the amount of benzoxazine containing hydrazide group is 60 mg; in component B, the amount of amino-modified hexagonal boron nitride added is 40 mg, and the amount of benzoxazine containing hydrazide group is 120 mg. Comparative Example
[0035] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, benzoxazine containing hydrazide group was not added in step (3).
[0036] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that no graphene dispersion was added in step (3) of Comparative Example 2.
[0037] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, amino-modified hexagonal boron nitride was not added in step (3). Performance testing
[0038] The products were prepared according to Examples 1-3 and Comparative Examples 1-3. The 1H NMR spectrum of the benzo[a]azine containing hydrazide group in Example 1, the TGA image of the benzo[a]azine resin obtained by direct curing of the benzo[a]azine containing hydrazide group obtained in step (1) and the electromagnetic shielding thermal conductive film, the SEM image of the electromagnetic shielding thermal conductive film, and the comparison diagram of the electromagnetic shielding thermal conductive film at 8-12Hz are shown in Figures 1-4. The electromagnetic shielding thermal conductive films prepared in Examples 1-3 and Comparative Examples 1-3 were also tested, and the 5% weight loss temperature T of the film was recorded. d5 10% weight loss temperature T d10 The carbon residue Yc, thermal conductivity, and electrical conductivity at 800℃ are shown in Table 1.
[0039] Table 1 Performance Tests of Thermally Conductive Thin Films Example 1 337.3 390.1 71.5 24.5 <![CDATA[1.53×10 -4 ]]> 73.7 Example 2 362.3 440.6 81.8 33.1 <![CDATA[8.74×10 -4 ]]> 85.3 Example 3 313.6 355.7 62.2 13.7 <![CDATA[3.56×10 -4 ]]> 54.1 Comparative Example 1 —— —— —— —— —— —— Comparative Example 2 293.1 325.1 45.6 5.6 0 38 Comparative Example 3 312.5 345.8 58.9 25.1 <![CDATA[2.32×10 2 ]]> 71.6 according to Figure 1-4 As can be seen from Table 1, Examples 1-3 and Comparative Examples 1-3, the electromagnetic shielding thermally conductive films prepared in Examples 1-3 have excellent high-temperature resistance, thermal conductivity, electromagnetic shielding performance and adjustable electrical conductivity. In addition, the film structure is complete and the interlayer bonding is tight, which shows good application prospects in the fields of electromagnetic shielding and thermal management.
[0040] Figure 1 The image shows the 1H NMR spectrum of the benzoxazine containing an acylhydrazine group obtained in step (1) of Example 1. It can be clearly seen from the image that distinct characteristic peaks appear near chemical shifts of 4.95 ppm and 4.27 ppm, corresponding to the resonance absorption of two different hydrogen atoms of the methylene group on the benzoxazine ring. The appearance of these characteristic peaks indicates that the reaction proceeded successfully and the benzoxazine ring structure was successfully formed, proving that the target product, the benzoxazine monomer containing an acylhydrazine group, was successfully synthesized.
[0041] Figure 2 The graph shows the thermogravimetric analysis (TGA) results of the cured benzoxazine resin and the composite film material in Example 1. The graph shows the 5% weight loss temperature T after polymerization of the benzoxazine resin. d5 The temperature is 283.7℃, and the 10% weight loss temperature is T. d10 The temperature was 301.7℃, and the char residue Yc at 800℃ was 40.5%; while the T of the cured composite film... d5 Significantly increased to 337.3℃, Td10 The temperature was increased to 390.1℃, and the Yc value was significantly improved to 71.5%. The thermal stability of the composite film is significantly better than that of pure benzoxazine resin. This is because graphene and boron nitride themselves have excellent thermal stability, and a tight organic-inorganic hybrid structure is formed under the connection of the benzoxazine crosslinking network. The thermal decomposition temperature of graphene and hexagonal boron nitride exceeds 800℃, forming a physical barrier layer inside the film, delaying the intrusion of oxygen and heat conduction into the matrix. At the same time, the hydrazide-containing benzoxazine forms a strong interfacial interaction with the two types of fillers, increasing the density of the cured crosslinking network. This dual effect inhibits the high-temperature chain segment breakage and decomposition of the polymer, simultaneously improving the thermal decomposition temperature and high-temperature char residue. The excellent high-temperature resistance allows the film to operate stably for a long time in high-temperature environments such as high-power electronic devices and automotive electronic control units.
[0042] Figure 3 This is a scanning electron microscope (SEM) image of the electromagnetic shielding composite film prepared in Example 1. The image clearly shows a highly ordered, layered stacked structure. The sheet-like graphene and boron nitride fillers are oriented in an in-plane direction perpendicular to the filtration direction during vacuum filtration. The thickness of the composite film is approximately 89 μm. This unique oriented layered structure is key to the film's excellent electromagnetic shielding and thermal conductivity: when electromagnetic waves are incident on the sandwich film, firstly, the conductive graphene layer in the middle absorbs electromagnetic wave energy due to conductivity loss; secondly, repeated reflection and scattering occur at multiple interfaces between layers, extending the electromagnetic wave transmission path and further dissipating energy. The insulating boron nitride layers on both sides block the conductive path, preventing overall film conductivity from causing short circuits in the equipment. The total shielding effectiveness is the sum of reflection loss and absorption loss. Simultaneously, the oriented sheet-like fillers construct a continuous thermally conductive path along the in-plane direction, facilitating rapid heat conduction.
[0043] Figure 4 The graph shows a comparison of the electromagnetic shielding efficiency of the composite film prepared in Example 1 within the 8-12 GHz frequency range. As can be seen from the graph, the composite film exhibits excellent electromagnetic shielding performance throughout the entire test frequency band, with a consistently high shielding efficiency across the entire X-band. This is attributed to the multiple reflection dissipation mechanism within the film and the excellent conductivity of graphene. Example 1 achieved an electromagnetic shielding efficiency of 73.7 dB, while Example 2 further improved this to 85.3 dB, far exceeding the 20 dB typically required for commercial applications, thus classifying it as an excellent electromagnetic shielding material.
[0044] Compared with Example 2, Example 2's T d5 T d10Both the carbon residue and the thermal conductivity were higher than those of Example 1, but the electrical conductivity increased slightly. In step (3) of Example 2, a lower amount of benzoxazine containing hydrazide was added. The relative content of benzoxazine as a connecting medium was reduced, and the direct contact between the fillers was more sufficient, which was beneficial to phonon transmission and electron hopping. Therefore, the thermal conductivity and electrical conductivity were improved. At the same time, the crosslinking density of benzoxazine was relatively reduced, but the thermal stability of the filler itself was high, and the overall heat resistance remained at a good level.
[0045] Compared with Example 1, the T value of Example 3 is different. d5 T d10 The residual carbon content decreased significantly, and the thermal and electrical conductivity also decreased significantly. Example 3 significantly increased the amount of benzoxazine containing hydrazide groups. Excessive benzoxazine coated the surface of graphene and boron nitride, which to some extent hindered the direct contact and network connectivity between fillers, resulting in a decrease in thermal and electrical conductivity. At the same time, although the crosslinking density increased due to the high content of benzoxazine containing hydrazide groups, its intrinsic thermal stability was lower than that of inorganic fillers, so the overall heat resistance of the film was reduced.
[0046] Compared with Example 1, Comparative Example 1 did not add benzoxazine monomers containing hydrazide groups in step (3). The resulting film cracked due to the lack of connecting medium between the layers and could not form a complete film. This shows that benzoxazine containing hydrazide groups not only serves as a matrix material in the system, but more importantly, it connects the graphene and boron nitride layers together through conjugation and hydrogen bonding. In the subsequent thermosetting process, it further enhances the interlayer bonding force through ring-opening crosslinking. It is the core component that ensures the integrity of the film structure and mechanical properties.
[0047] Compared with Example 1, Comparative Example 2 did not add graphene. Although the resulting film was non-conductive and had good insulation properties, its thermal conductivity was only 5.6 W / mK, and its heat resistance was significantly reduced. The electromagnetic shielding effectiveness was 38 dB. This indicates that graphene played a major role in constructing the heat conduction channel and absorbing electromagnetic waves in the system. Without graphene, the thermal conductivity network formed by boron nitride alone was less efficient, and the electromagnetic shielding effectiveness was also greatly reduced, making it difficult to meet the needs of practical applications.
[0048] Compared to Example 1, Comparative Example 3 did not add boron nitride. Although the resulting film had higher thermal conductivity and heat resistance similar to Example 1, its electrical conductivity was as high as 2.32 × 10⁻⁶. 2 S / cm, belonging to conductive materials, poses a significant risk of leakage when used as electromagnetic shielding materials for electronic devices. This indicates that the introduction of boron nitride is crucial to ensuring the electrical insulation of the thin film. At the same time, the hydrogen bonding between boron nitride and benzoxazine also helps to regulate the microstructure and mechanical properties of the thin film.
[0049] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A high-temperature resistant electromagnetic shielding thermally conductive film, characterized in that: The raw materials include: benzoxazine containing an acylhydrazine group, graphene, and boron nitride, wherein the structure of the benzoxazine containing the acylhydrazine group is shown below: .
2. A method for preparing a high-temperature resistant electromagnetic shielding thermally conductive thin film as described in claim 1, characterized in that: Includes the following steps: (1) Add isophthalic acid dihydrazide, phenol and paraformaldehyde to an organic solvent, heat to react, filter the reactants after the reaction, wash the filtrate and dry it by rotary evaporation to obtain a solid product, which is benzoxazine containing hydrazide group; (2) Boron nitride and urea were ball-milled, centrifuged and dried to obtain amino-modified hexagonal boron nitride; (3) The benzoxazine containing hydrazide group obtained in step (1) is mixed and stirred with graphene dispersion and amino-modified hexagonal boron nitride obtained in step (2). The mixture is then filtered through vacuum and self-assembled into a film. Finally, it is heated and cured to obtain an insulating electromagnetic shielding composite film material.
3. The method for preparing a high-temperature resistant electromagnetic shielding thermally conductive thin film according to claim 2, characterized in that: In step (1), the molar ratio of isophthalic acid dihydrazide, paraformaldehyde, and phenol is 1:(4-4.4):
2.
4. The method for preparing a high-temperature resistant electromagnetic shielding thermally conductive thin film according to claim 2, characterized in that: In step (1), the organic solvent is selected from any one of toluene, N-methylpyrrolidone or N,N-dimethylformamide; the heating reaction temperature is 80-120℃ and the time is 6-10h.
5. The method for preparing a high-temperature resistant electromagnetic shielding thermally conductive thin film according to claim 2, characterized in that: In step (2), the mass ratio of boron nitride to urea is 1:30; centrifugation is performed twice, with the first centrifugation speed being 1000-2500 rpm and the second centrifugation speed being 8000-10000 rpm.
6. The method for preparing a high-temperature resistant electromagnetic shielding thermally conductive thin film according to claim 2, characterized in that: In step (3), the mass ratio of boron nitride to benzoxazine containing hydrazide is 1:(0.5-3), the mass ratio of graphene to benzoxazine containing hydrazide is 1:(0.25-4), and the mixture is stirred at room temperature for 17-24 hours.
7. The method for preparing a high-temperature resistant electromagnetic shielding thermally conductive thin film according to claim 2, characterized in that: In step (3), the vacuum filtration self-assembly is performed by filtration in a Buchner core funnel, and the resulting film is dried in a vacuum drying oven.
8. The method for preparing a high-temperature resistant electromagnetic shielding thermally conductive thin film according to claim 2, characterized in that: In step (3), the specific heating process for curing is as follows: heating to 140℃ and holding for 1 hour, 160℃ and holding for 1 hour, 180℃ and holding for 1 hour, 200℃ and holding for 1 hour, and 240℃ and holding for 1 hour in sequence.
9. The application of the high-temperature resistant electromagnetic shielding thermally conductive film as described in claim 1 in chip packaging and protective materials for the electronic control unit of new energy vehicles.